Kebijakan Pendidikan Bermotif Politik: Pengembangan Pendidikan Dasar Melalui Pembagian Laptop Gratis di Kabupaten Badung, Bali - Agus Putra Mahendra; I Nyoman Darma Putra; Ida Bagus Gede Pujaastawa (Universitas Udayana, 2020)
This paper analyzes the policy of distributing free laptops by the Badung Regency Government, Bali, to all 5th and 6th grade students at the public elementary school, but not to students at private school, in Badung Regency, Bali, since 2016 to develop basic education in the region. This topic is researched because it is a public policy development of basic education that was first implemented in Bali. The problem studied is how the response of stakeholders in the public elementary and private elementary schools to the policy. Data was obtained based on the results of interviews, document studies, and observations which were then analyzed by Hermeneutics theory and the Power of Knowledge. The analysis produced three conclusions. First, the policy was responded positively by supporters of the interests of public elementary schools. Second, the policy was responded to as a discriminatory policy by private elementary school stakeholders. Third, education policy is political sense for the interests of the authorities.